The Effect of Enhanced External Counterpulsation on the Vascular State, Indicators of Glycemic Control and Quality of Life in Patients with Coronary Artery Disease and Type 2 Diabetes Mellitus - O. A. Slepova; A. S. Lishuta; E. Yu. Vasiltsova; E. V. Privalova; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of enhanced external counterpulsation (EECP) on the functional status, quality of life, structural and functional state of the vascular bed, and markers of glycemic control in patients with coronary artery disease (CAD) and type 2 diabetes mellitus (DM).Material and methods. A pilot prospective randomized study included 30 patients with CAD and DM. Using a random number generator, patients were randomized into 2 groups: EECP (n=15) and a comparison group (n=15). All patients (n=30) received optimal medical therapy (OMT) during 3 months of follow-up. Patients in the EECP group underwent a course of EECP (35 hours, cuff pressure: 220-280 mmHg) during the first 7 weeks of the study. At baseline and after 3 months of follow-up, patients in both groups underwent an assessment of clinical status, quality of life (based on the SF-36 questionnaire), as well as a 6-minute walk test to assess exercise tolerance. The dynamics of fasting glucose, postprandial glucose, insulin resistance index (HOMA-IR) and glycated hemoglobin were assessed. Photoplethysmography and applanation tonometry were performed to assess the state of the vascular bed.Results. In the EECP group, after 3 months, there was a decrease in the frequency of angina attacks and an improvement in the functional class of angina according to the Canadian Cardiovascular Society (CCS) classification. A significant improvement in exercise tolerance was revealed [an increase in the 6-minute walking distance by 51 (35; 65) m, p<0.05], as well as an improvement in the physical and mental components of health according to the SF-36 questionnaire. A positive dynamics was shown in relation to the indicators of the state of both large vessels and the microvasculature (p>0.05), with the exception of the reflection index and the stiffness index (p<0.05). There was also a significant decrease in the HOMA-IR [-9.9% (-26.5; -4.0) vs 7.7% (-7.9; 13.8), p=0.004], as well as in the levels of fasting glucose [-10.5% (-15.8; -4.0) vs -2.7 (-8.3; 5.9), p=0.012] in the EECP group, compared with the OMT group.Conclusion. EECP course therapy in addition to OMT has a positive effect on the functional status and quality of life of patients with CAD and DM. After 3 months of observation, there was noted a positive dynamics of the vascular state, as well as markers of glycemic control, and these changes were more pronounced in the EECP group. The results obtained may indicate the effectiveness of EECP as an add-on treatment for this group of patients.